Clinical characteristics of invasive disease caused by a rare Group A Streptococcus subtype (emm26.3) — Alaska, 2016–2017. (4th October 2017) - Mosites, Emily; Frick, Anna; Gounder, Prabhu; Castrodale, Louisa; Rudolph, Karen; Lecy, K Danielle; Zulz, Tammy; Mclaughlin, Joseph; Hennessy, Thomas; Bruce, Michael
Abstract: Background: Clinical manifestations of Group A Streptococcus invasive disease (iGAS) can vary by molecular subtype ( emm type). In Alaska, we complete emm typing and antimicrobial susceptibility testing for all isolates received by the statewide iGAS surveillance system. In February 2016, we identified a rare subtype, emm 26.3, which had not been detected in Alaska previously. We compared the clinical characteristics of emm 26.3 iGAS cases with those caused by other emm types. Methods: We defined a case as the isolation of GAS from a normally sterile body site in an Alaska resident from February 2016 to April 2017. We also included non-sterile site GAS isolates if the cases had a diagnosis of necrotizing fasciitis (NF) or streptococcal toxic shock syndrome (STSS). We requested medical records for all cases caused by emm 26.3 and for cases of iGAS caused by non- emm 26.3 types that were admitted to the same healthcare facility within three months of each emm 26.3 case. We collected demographic, clinical, and laboratory data by using a standard chart abstraction form. We calculated P -values using logistic and linear regression. Results: We reviewed records for 53 cases of emm 26.3 and 47 cases of other emm types (including emm 1, 4, 11, 12, 49, 59, 81, and 91). Cases of emm 26.3 had a mean age of 52 years; 37 (70%) were male and 41 (82%) were Alaska Native. Emm 26.3 cases were more likely to have underlying alcohol use disorders than adult cases of other emm types (72% vs. 41%, P < 0.01). Emm 26.3 cases had significantly longer durations of hospitalization (median 11 days vs. 5 days, P = 0.01) and were more likely to have GAS bacteremia (55% vs. 32%, P = 0.02). The case fatality for emm 26.3 was 9% (vs. 4% among non- emm 26.3 cases, P = 0.31). Severe disease diagnoses included sepsis (51% vs. 38%), NF (26% vs. 11%), and STSS (9% vs. 6%). Diagnosis with any of these severe diseases was higher among emm 26.3 cases than non- emm 26.3 types ( P = 0.02). Emm 26.3 isolates were susceptible to ceftriaxone, penicillin, and erythromycin. Conclusion: Emm 26.3 GAS is associated with severe invasive disease. Reasons for this could include characteristics of the bacterium or of the affected population. Further investigation into the virulence of the bacterium is warranted. Disclosures: All authors: No reported disclosures.